2016
DOI: 10.21873/anticanres.11152
|View full text |Cite
|
Sign up to set email alerts
|

Heart Peptide Hormones: Adjunct and Primary Treatments of Cancer

Abstract: Abstract. Four heart hormones, namely atrial natriuretic peptide (ANP), long-acting natriuretic peptide (LANP), these pathways and their crosstalk is inhibited by these peptide hormones. They enter the nucleus of cancer cells where they inhibit the proto-oncogenes c-FOS (by up to 82%) and c-JUN (by up to 61%). Conclusion: These multiple kinase inhibitors have both adjunct and primary anticancer effects.The amino acid sequences of atrial natriuretic peptide (ANP) and the ANP prohormone from which it is derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Atrial natriuretic peptide (ANP) has been shown to inhibit tumor growth in vitro and in vivo studies [ 27 , 28 ]. ANP belongs to a family of cardiac and vascular-derived peptide hormones that plays a crucial role in cardiovascular homeostasis through blood pressure and volume regulation [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atrial natriuretic peptide (ANP) has been shown to inhibit tumor growth in vitro and in vivo studies [ 27 , 28 ]. ANP belongs to a family of cardiac and vascular-derived peptide hormones that plays a crucial role in cardiovascular homeostasis through blood pressure and volume regulation [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a thorough search in the literature resulted in 758 publications on the subject. Natriuretic peptides can inhibit the progression of pancreatic-, breast-, small cell lung-, and prostate cancer in vivo and in vitro [ 45 ] and have been proposed as primary treatments for cancers [ 46 , 47 , 48 ] since they cause the death of cancer cells without affecting healthy cells [ 29 , 49 , 50 , 51 ]. Mechanisms underlying the anti-cancer effects of natriuretic hormones are based on the inhibition of conversion of GDP-Ras to GTP-Ras, one of the main pathways in cancer formation, and on the cGMP-mediated inhibition of the Ras-MEK 1/2-ERK 1/2 kinase cascade.…”
Section: Natriuretic Peptides and Cancermentioning
confidence: 99%
“…Mechanisms underlying the anti-cancer effects of natriuretic hormones are based on the inhibition of conversion of GDP-Ras to GTP-Ras, one of the main pathways in cancer formation, and on the cGMP-mediated inhibition of the Ras-MEK 1/2-ERK 1/2 kinase cascade. Furthermore, the hormones inhibit the crosstalk between Ras-MEK 1/2-ERK 1/2 kinase cascade and the pathways of VEGF, β-catenin, JNK, WNT, and STAT3, leading to the inhibition of the proto-oncogenes c-FOS and c-JUN in the nucleus of cancer cells [ 48 , 49 ] ( Figure 3 ). Given that tumor progression and malignancy also require the preservation of extracellular acidosis, cancer cells overexpress on their membrane several pH regulators.…”
Section: Natriuretic Peptides and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide inhibits the growth of smooth myocytes, endothelial cells, and the activity of fibroblasts [9]. The peptide is involved in the differentiation of cardiac myocytes [10], reduces hypertrophy [11], has anti-inflammatory effect, and so on [12]. The definition of ANP concentration in the blood has diagnostic and prognostic value [13].…”
Section: Introductionmentioning
confidence: 99%